2013
DOI: 10.2478/s11658-013-0108-x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential-dependent binding of polysialic acid to lipid monolayers and bilayers

Abstract: Abbreviations used:  diff -potassium diffusion potential,  S -surface potential; DP -degree of polymerization; ODA -octadecylamine; polySia -polysialic acid; OX-Voxonol V, TB -toluidine blue Abstract: Polysialic acids are linear polysaccharides composed of sialic acid monomers. These polyanionic chains are usually membrane-bound, and are expressed on the surfaces of neural, tumor and neuroinvasive bacterial cells. We used toluidine blue spectroscopy, the Langmuir monolayer technique and fluorescence spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…These results are consistent with a reduction of negatively charged polySia chains at the outer exosomal surface after the Endo‐N treatment. The estimated change in the transmembrane potential value, based on OX‐V calibration curve for liposomes [39], is ca. −30 mV after 115 min of Endo‐N treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with a reduction of negatively charged polySia chains at the outer exosomal surface after the Endo‐N treatment. The estimated change in the transmembrane potential value, based on OX‐V calibration curve for liposomes [39], is ca. −30 mV after 115 min of Endo‐N treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that the removal of polySia chains from the exosomal surface by Endo‐N makes membrane surface potential more positive, transmembrane potential more negative, and the activation energy for membrane anisotropy changes reduced. The modulation of membrane potentials by polySia chains can affect both function of membrane proteins embedded in the exosomal membranes and the interaction of exosomes with plasma membranes [39]. Next, we studied the differences between the abundance of polysialylated exosomes in FBS (fetal bovine serum) and in CBS (calf bovine serum).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spector and Yorek believed that the best approach in the study of such alteration is to make functional observations with cultured cells and then explore the mechanism producing these effects with either a reconstituted system or isolated membranes modified by incubation with liposomes [60]. However, this approach needs not only a detailed analysis of the linkages between theoretical and experimental studies, but also different methods to evaluate cell membrane properties [61][62][63]. Ageing can also influence the cell membrane composition.…”
Section: Discussionmentioning
confidence: 99%
“…Nowotarski et al [113] showed that the electrical profile of the membrane is also relevant More complex materials such as polysaccharide-protein complexes extracted from fungi or algae were made to interact with charged lipids to probe possible therapeutic actions [114,115]. Schmidt et al [114] showed that the very slightly surface active protein- Langmuir monolayers of cholesterol/DPPC = 0.9 [117] or as more complicated ternary and quaternary mixtures [118] with different compositions of its inner and outer leaflets.…”
Section: Other Polysaccharidesmentioning
confidence: 98%